2013
DOI: 10.1111/bpa.12043
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRA Amplification is Common in Pediatric and Adult High‐Grade Astrocytomas and Identifies a Poor Prognostic Group in IDH1 Mutant Glioblastoma

Abstract: High-grade astrocytomas (HGAs), corresponding to WHO grades III (AA) and IV (GBM), are biologically aggressive and their molecular classification is increasingly relevant to clinical management. PDGFRA amplification is common in HGAs, although its prognostic significance remains unclear. Using fluorescence in situ hybridization (FISH), the most sensitive technique for detecting PDGFRA copy number gains, we determined PDGFRA amplification status in 123 pediatric and 263 adult HGAs. A range of PDGFRA FISH patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…35 In a recent study, PDGFRA amplification was seen in 23% of GBM cases and demonstrated a significant reduction in median survival in only the IDH1 mutation subgroup (16.0 vs 72.6 months). 38 Despite the importance of PDGF in GBM proliferation-as it is found upstream of important signaling pathways such as AKT, involved with in vitro growth of GBM, and used in animal models of GBM-no definitive role in predicting prognosis has been seen in clinical studies. In one study of 65 cases of GBM, PDGFRA amplification was detected in only 1 case.…”
Section: Platelet-derived Growth Factor Receptor (Pdgfr)mentioning
confidence: 99%
“…35 In a recent study, PDGFRA amplification was seen in 23% of GBM cases and demonstrated a significant reduction in median survival in only the IDH1 mutation subgroup (16.0 vs 72.6 months). 38 Despite the importance of PDGF in GBM proliferation-as it is found upstream of important signaling pathways such as AKT, involved with in vitro growth of GBM, and used in animal models of GBM-no definitive role in predicting prognosis has been seen in clinical studies. In one study of 65 cases of GBM, PDGFRA amplification was detected in only 1 case.…”
Section: Platelet-derived Growth Factor Receptor (Pdgfr)mentioning
confidence: 99%
“…Herein, we hypothesized that additional “tertiary” genetic alterations, which have been noted to occur in IDH -mutant gliomas (7, 15, 26, 27), could be the drivers of the progressive malignant phenotype of IDH -mutant gliomas. We therefore tested 20 consecutive IDH -mutant glioma specimens from patients undergoing surgery at our institution for the ability to establish intracerebral xenografts in mice.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations were associated with biological progression and shorter progression-free survivals (Bettegowda et al, 2011;Broderick et al, 2004;Wakimoto et al, 2014). IDH-mutated GBMs have a higher frequency of PDGFRA amplification compared to IDH wild-type GBMs, while this alteration is uncommon in lower grade IDH mutant astocytomas, suggesting it may be a lineage specific marker of progression (Burford et al, 2013;Phillips et al, 2013). CDKN2A deletion also occurs in a subset of IDH-mutant gliomas that have TP53 mutation, as well as a small subset with 1p/19q co-deletion, and has been proposed as a marker of progression (Bigner et al, 1999;Reyes-Botero et al, 2014).…”
Section: Primary Vs Secondary Glioblastomamentioning
confidence: 99%